2013
DOI: 10.1371/journal.pone.0071796
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Size of HIV Key Affected Populations in Chongqing, China, Using the Network Scale-Up Method

Abstract: ObjectivesTo estimate the average social network size in the general population and the size of HIV key affected populations (KAPs) in Chongqing municipality using the network scale-up method (NSUM).MethodsA general population survey was conducted in 2011 through a multistage random sampling method. Participants aged between 18 and 60 years were recruited. The average social network size (c) was estimated and adjusted by known population method. The size of HIV KAP in Chongqing municipality was estimated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 12 publications
2
44
0
1
Order By: Relevance
“…Our result were closer to Harbin city but below Beijing city. And the study of Guo W [ 25 ] used the method of NSUM which produce the similar result to ours. Based on these results, we may identify some similarities by different methods.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our result were closer to Harbin city but below Beijing city. And the study of Guo W [ 25 ] used the method of NSUM which produce the similar result to ours. Based on these results, we may identify some similarities by different methods.…”
Section: Discussionsupporting
confidence: 55%
“…The current study focused on HIV/AIDS high-risk populations and estimated the size of MSM populations in Shanghai, China, to be 36354 with a plausible range of 28489–44219 by using the NSUM. To date, two studies have used the NSUM to estimate the MSM population size including one from China [ 25 ]. Our results are comparable to the previous study in Chongqing, China, which demonstrated similar prevalence of MSM among male population [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using World Bank’s designation (90) for country income level, most studies (k=50, 86%) were conducted in high-income countries, three studies in upper middle-income countries (62, 65, 68), four studies in lower middle-income (66, 73, 76, 80), and none in low-income countries. Fifty-one studies (88%) were conducted in the United States, Canada, or Europe, four studies in East and Southeast Asia (68, 76, 77, 85), three in Central America (50, 56, 65), one in South Africa (62), and no studies were conducted in Australia or South America (Figure 2). The studies that focused on HIV prevention were primarily conducted in the United States or Europe (88%), with few in South-Southeast Asia, Central America, and Africa.…”
Section: Resultsmentioning
confidence: 99%
“…Chongqing is one of the four municipalities under the direct control of the central government of China and serves as the economic and political center of southwest China, which has made Chongqing a magnet for migrant workers [27,28]. The average annual rate for new HIV infections in Chongqing from 2007 to 2012 was 19.7%, which greatly exceeded the national infection rate (3.13%) [29]. To augment the limited studies on MMWs in Chongqing, the present study adopted serial cross-sectional surveys to explore the prevalence of HIV, syphilis, and HCV among this group and investigated their HIV-related knowledge and behaviors from 2010 to 2018.…”
Section: Introductionmentioning
confidence: 99%